The Emotion of Pain for a Critical Theory of Society (Itinera, 2018)
Pain, as a physical and emotional experience, is an involuntary and unpleasant response to a situation, namely an external manifestation of an unintentional aversion to reality. This paper discusses the social aspects of pain that are relevant to political philosophy, insofar as the concept of pain can be considered as an effective parameter to define a society. It will be argued that if pain in our society is experienced as private, the experience of solidarity can only be shared with people and situations with whom we can identify.  In order to understand the emotional distance of many injustices in the world, the need for an awareness of human beings’ involvement in other people’s suffering is critical.